Antiphospholipid Antibodies in Non-Hodgkin's Lymphoma - Sanda BURUIANA; Maria ROBU; Victor TOMACINSCHII; Minodora MAZUR; Lucia MAZUR-NICORICI (Documenta Haematologica)
Introduction: Non-Hodgkin's lymphomas (NHL) are a heterogeneous group of malignant lymphoid tumors. Anticardiolipin (aCL), anti-β2 glycoprotein I (antiβ2GPI), lupus anticoagulant (LA) antibodies are found as NHL-associated acquired thrombophilic factors. Seropositivity of these antibodies in malignancies could remain asymptomatic. Despite these findings, the utility of routine testing for aCL, antiβ2GPI, LA antibodies in patients with NHL remains uncertain. Objective: This study aims to assess the prevalence of aCL, antiβ2GPI, LA antibodies in patients with nonHodgkin’s lymphomas depending on age, gender, type of NHL, stage, B symptoms, onset of the disease. Material and methods: A total of 161 patients diagnosed with NHL at the Oncology Institute of the Republic of Moldova were evaluated. Antibodies aCL IgM and IgG, antiβ2GP I IgM and IgG were estimated by enzymelinked immunosorbent assay (ELISA), and LA by the turbidimetry. Results: The prospective descriptive cross-sectional study included 161 de novo patients 48% women and 52% men, aged between 24 and 82 years, with aggressive (56.5%) and indolent (43.5%) NHL, with higher prevalence of generalized stages (III and IV) in 65.8%. aCL, antiβ2GPI and LA antibodies were recorded in 16.2% with increased incidence in aggressive, B-cell and gender-specific NHL. During the treatment, a tendency towards antibody negativity was observed. Conclusions: The prevalence of aCL, antiβ2GPI and LA antibodies in patients with NHL is higher than in the general population (16.2%), being expressed by single positivity in 14.3%, double positivity in 1.3%, and triple positivity in 0.6% isolated in B cell NHL. A statistically significant difference in antibody positivity was observed based on age and NHL type. Statistically insignificant was the distribution of patients with NHL associated with antibody synthesis according to gender, the degree of dissemination, B symptoms and the location of the primary tumor focus. During the treatment, a tendency of antibody negativity was observed.